EFEK MODERASI KEBIJAKAN DIVIDEN DALAM PENGARUH PROFITABILITAS TERHADAP NILAI PERUSAHAAN - Zarah Puspitaningtyas (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2017)
Corporate value is a condition that describes the achievement of a company during the process of operation. Increased corporate value is an achievement that reflects an increase in wealth for shareholder. The purpose of this study is to determine the effect of moderation dividend policy in the influence of profitability to the value of the company in manufacturing companies listed on the Indonesia Stock Exchange period 2012-2016. Based on purposive sampling technique, there are 24 companies that meet the criteria as the research sample. Data analysis was done by using moderated regression analysis method. The results of the analysis prove that, at the 5% level of significance, dividend policy is not able to moderate the effect of profitability on firm value.